2023
DOI: 10.1002/ijc.34424
|View full text |Cite
|
Sign up to set email alerts
|

A Phase IIb, single arm, multicenter trial of sacituzumab govitecan in Chinese patients with metastatic triple‐negative breast cancer who received at least two prior treatments

Abstract: Refractory or relapsing metastatic triple‐negative breast cancer (mTNBC) has a poor prognosis. Sacituzumab govitecan (SG) is a novel antibody‐drug conjugate, targeting human trophoblast cell‐surface antigen 2 (Trop‐2). This is the first report of SG's efficacy and safety in Chinese patients with mTNBC. EVER‐132‐001 (NCT04454437) was a multicenter, single‐arm, Phase IIb study in Chinese patients with mTNBC who failed ≥2 prior chemotherapy regimens. Eligible patients received 10 mg/kg SG on Days 1 and 8 of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…A single‐arm multicenter study reported one patient who died from shock during the third treatment cycle. Prior to the onset of shock, this patient experienced sacituzumab govitecan–related diarrhea and bone marrow suppression, which led to severe and refractory diarrhea‐induced hypovolemia, shock, and multiorgan failure, considered as a potential contributing factor to the fatal outcome 4 . Therefore, healthcare professionals should advise patients to seek medical attention immediately if diarrhea occurs to prevent irreversible body harm.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A single‐arm multicenter study reported one patient who died from shock during the third treatment cycle. Prior to the onset of shock, this patient experienced sacituzumab govitecan–related diarrhea and bone marrow suppression, which led to severe and refractory diarrhea‐induced hypovolemia, shock, and multiorgan failure, considered as a potential contributing factor to the fatal outcome 4 . Therefore, healthcare professionals should advise patients to seek medical attention immediately if diarrhea occurs to prevent irreversible body harm.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The particular subtype, triple-negative breast cancer (TNBC), regarded as the most aggressive form, constitutes ~ 15% of all BC occurrences. 3,4 TNBC is characterized by low expression of estrogen receptor (ER), human epidermal growth factor receptor 2 (HER2), and progesterone receptor (PR). Thus, TNBC is insensitive to hormone therapies and epidermal growth factor receptor (EGFR) antagonists, necessitating chemotherapy as the principal therapeutic intervention.…”
Section: Postmarketing Safety Of Sacituzumab Govitecan: a Pharmacovig...mentioning
confidence: 99%
See 3 more Smart Citations